The impact of resistance to change on the performance of employees "A Survey study in the Ministry of Higher Education Hospitals in Syria" - Barhoom, Adeeb; Hassan, Fedaa; Saeed, Rasha (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aimed to identify the impact of the resistance to change (organizational , economic, social dimension) on the performance of employees in the Ministry of Higher Education Hospitals in Syria. Primary information were collected through a questionnaire was distributed to a simple random sample of research community, the data was analyzed by the SPSS statistical program. After the study and analysis the research reached to some of the important results: 1- There is a correlation relationship between the dimensions of the resistance to change (organizational , economic, social) and the performance of employees. 2- There is a significant impact of the organizational dimension, economic dimension and social dimension on the performance of employees. أثر مقاومة التغيير على أداء العاملين "دراسة مسحية على المشافي التابعة لوزارة التعليم العالي في سورية" هدفت هذه الدراسة إلى التعرف على أثر أبعاد مقاومة التغيير (البعد التنظيمي, البعد الاقتصادي, البعد الاجتماعي) على أداء العاملين في المشافي التابعة لوزارة التعليم العالي في سورية. تم جمع المعلومات الأولية للبحث من خلال استبيان تم توزيعه على عينة عشوائية بسيطة من مجتمع البحث, وتم تحليل هذه البيانات من خلال برنامج الـ SPSS الإحصائي. وبعد الدراسة والتحليل كان من أهم نتائج هذا البحث: 1- وجود علاقة ارتباط بين أبعاد مقاومة التغيير وأداء العاملين. 2- وجود تأثير معنوي للبعد التنظيمي والبعد الاقتصادي والبعد الاجتماعي على أداء العاملين في المشافي محل الدراسة.